A survey of evidence users about the information need of acupuncture clinical evidence. Issue 1 (December 2016) - Shi, Xiue; Wang, Xiaoqin; Liu, Yali; Li, Xiuxia; Wei, Dang; Zhao, Xu; Gu, Jing; Yang, Kehu
Abstract Background The PRISMA statement was rarely used in the field of acupuncture, possibly because of knowledge gaps and the lack of items tailored for characteristics of acupuncture. And with an increasing number of systematic reviews in acupuncture, it is necessary to develop an extension of PRISMA for acupuncture. And this study was the first step of our project, of which the aim was to investigate the need for information of clinical evidence on acupuncture from the perspectives of evidence users. Methods We designed a questionnaire based on a pilot survey and a literature review of acupuncture systematic review or meta-analysis(SR/MA). Participants from five cities (Lanzhou, Chengdu, Shanghai, Nanjing and Beijing) representing the different regions of China, including clinicians, researchers and postgraduates in their second year of Master studies or higher level, were surveyed. Results A total of 269 questionnaires were collected in 18 hospitals, medical universities and research agencies, and 251 (93 %) with complete data were used for analysis. The average age of respondents was 33 years (SD 8.959, range 25–58) with male 43 % and female 57 %. Most respondents had less than 5 years of working experience on acupuncture, and read only one to five articles per month. Electronic databases, search engines and academic conferences were the most common sources for obtaining information. Fifty-six percent of the respondents expressed low satisfaction of the completeness of information from the literature. The eight items proposed for acupuncture SR/MAs received all high scores, and five of the items scored higher than eight on a scale zero to ten. The differences for the scores of most items between postgraduates and non-postgraduates were not statistically significant. Conclusions The majority of the respondents were not very satisfied with the information provided in acupuncture SRs. Most of the items proposed in this questionnaire received high scores, and opinions from postgraduates and non-postgraduates tended to agree on most items. Comments from the respondents can promote future work.